Evaluation of bone marrow functions and new inflammatory markers in patients with immunocompetent herpes zoster - Esma İnan Yüksel; Demet Çiçek; Betül Demir; Ozan Erdem (Galenos Publishing House, 2023)
Background and Design: Herpes zoster (HZ) is a viral infection characterized by dermatomal vesicles caused by the reactivation of the latent varicella-zoster virus (VZV). There are conflicting reports regarding the effects of VZV on bone marrow functions. In this study, we aimed to evaluate bone marrow function and systemic inflammation in immunocompetent HZ patients. Materials and Methods: This study included patients aged ≥18 yr diagnosed with HZ and admitted to a dermatology outpatient clinic between June 2011 and June 2021. Hematological parameters in routine hemogram tests of patients with HZ and new inflammatory markers, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune inflammation index, and platelet-neutrophil ratio (PNR), were determined and compared with healthy control groups. Results: Thrombocytopenia was observed in 6.1% and lymphopenia in 8% of 461 HZ patients. The mean leukocyte (white blood cell), lymphocyte, neutrophil, eosinophil, and platelet (PLT) counts in HZ patients were statistically significantly lower than in the control group (p<0.05). NLR and PLR values were statistically significantly higher in HZ patients than in the control group (p<0.05). PLT, eosinophil count, and PNR values were statistically lower in HZ patients aged ≥65 yr than in patients aged <65 yr, whereas mean platelet volume and NLR values were higher (p<0.05). Conclusion: Thrombocytopenia and lymphopenia may occur in immunocompetent HZ patients. NLR and PLR values increase in HZ patients. The increase in inflammatory markers and decrease in platelet count are more evident in HZ patients aged ≥65 yr.